2010
DOI: 10.2298/avb1003257s
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of sows after intracervical or intrauterine insemination with different spermatozoa number in reduced volume doses

Abstract: Modern intensive pig production demands an increasing number of insemination doses per ejaculate of genetically superior boars. In order to achieve such a result the possibility of producing insemination doses in both reduced volume and spermatozoa count without decreasing the fertility of sows is studied. In this trial we studied the effect of insemination with reduced volumes of semen (50 mL) and varied spermatozoa count (4, 2 or 1x109). Insemination was performed by the classical (intracervical) or by the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The finding of the present study confirm the results of others in that intrauterine insemination with doses of various volumes (100, 85, 50, 30, and 20 mL) and spermatozoa counts (4, 3, 1.5, and 1 × 10 9 ), produced farrowing rates ranging from 78% to 96% with litter sizes of 9 to 12 live-born piglets (7)(8)(9)(10)(11)(12)(13)(14). Additionally, a key feature in the success of intrauterine insemination is the deposition of semen in the cranial parts of the female reproductive system (body of uterus, uterine horns, uterotubal junctions, or oviducts).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding of the present study confirm the results of others in that intrauterine insemination with doses of various volumes (100, 85, 50, 30, and 20 mL) and spermatozoa counts (4, 3, 1.5, and 1 × 10 9 ), produced farrowing rates ranging from 78% to 96% with litter sizes of 9 to 12 live-born piglets (7)(8)(9)(10)(11)(12)(13)(14). Additionally, a key feature in the success of intrauterine insemination is the deposition of semen in the cranial parts of the female reproductive system (body of uterus, uterine horns, uterotubal junctions, or oviducts).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported that optimal farrowing rates in sows could be achieved if insemination is performed around 24 h before ovulation, with doses containing 2 × 10 9 spermatozoa. An increase in the number of spermatozoa above this value has no impact on the achieved fertility, whereas a reduction in the number of spermatozoa below 2 × 10 9 results in lowered fertility in inseminated sows (4,10,19). Those studies showed that with intrauterine insemination, doses of onehalf of the volume and the number of spermatozoa that are employed with classic intracervical insemination will produce a satisfactory farrowing rate and litter size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fertility of liquid-stored boar semen depends mainly on the following factors: initial ejaculate quality and frequency of semen collection, extender type, storage temperature and duration, sperm number per AI dose, insemination volume, number and timing of inseminations relative to ovulation at each estrus as well as the site of semen deposition in the female genital tract (16,39,45,(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). In addition, a number of factors can also influence the fertility levels in pig farms, including boar breed and age, parity and lactation length, weaning-toestrus interval, season, stress, nutritional status and inseminator skills (80,85,86,88,91,(93)(94)(95)(96)(97)(98)(99)(100).…”
Section: Principle S Behind Anaerobic Storage Of Semen At 15-20 O Cmentioning
confidence: 99%